2010
DOI: 10.3892/ijo_00000644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential calcium sensing receptor inducers on promoting chemosensitivity of human colon carcinoma cells

Abstract: Abstract.We have previously reported that by inducing calcium sensing receptor (CaSR), calcitriol, the active form of vitamin D, promoted the sensitivity of the human colon carcinoma cells to anticancer drugs. In the current study we tested several other potential CaSR modulators, calcipotriol and the effective components of Chinese herbal medicine lentinan, for their functions in inducing CaSR expression in human colon carcinoma cell line CBS, Moser, Fet, and SW480 cells and subsequently promoting sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…RT-PCR revealed that all cell lines investigated expressed CD97, however with different isoform distribution (EGF1,2,5; EGF1,2,3,5 and EGF1-5) (Figure 1A). As demonstrated before [19], BGC-823 cells had the lowest intensity of CD97/EGF1,2,5 but the strongest intensity of CD97/EGF1-5, while AGS showed the strongest expression of CD97 small isoform but the weakest of CD97 big isoform. SGC-7901 which expressed moderate levels of both CD97 small and big isoforms was selected to investigate the specific effects of CD97 small isoform (Figure 1C-D).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…RT-PCR revealed that all cell lines investigated expressed CD97, however with different isoform distribution (EGF1,2,5; EGF1,2,3,5 and EGF1-5) (Figure 1A). As demonstrated before [19], BGC-823 cells had the lowest intensity of CD97/EGF1,2,5 but the strongest intensity of CD97/EGF1-5, while AGS showed the strongest expression of CD97 small isoform but the weakest of CD97 big isoform. SGC-7901 which expressed moderate levels of both CD97 small and big isoforms was selected to investigate the specific effects of CD97 small isoform (Figure 1C-D).…”
Section: Resultssupporting
confidence: 76%
“…The cells bearing CD97/EGF1,2,5 insert revealed increased invasive behavior, while the cells over-expressing CD97/EGF1-5 long isoform demonstrated tumor suppressive properties [19]. Other investigations concering CD97 variants revealed that over-expression of CD97/EGF1,2,5 insert propagated invasion of colon cancer cells, while C-terminal insertion reduced it.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The present study clearly shows the expression specificity of this receptor in GBM cancer cells compared to non-cancerous neural cells. Further studies need to be performed to establish which of the possible splice variants [52] are upregulated. So far there are no reports on the physiological role of CD97 in brain.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric tumor tissues, the expression of CD55 was well correlated with that of CD97. Particularly, strong staining of CD97 and CD55 was observed in the cytoplasm of the signet ring cell carcinoma of patients, which suggests that CD97 may be involved in the remodelling of adhesive contacts of the invading tumor cells by direct receptor-ligand interactions [18]. In colorectal carcinomas, CD97 and CD55 are overexpressed in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%